E-commerce – trends and development opportunities - Radziszewska, Aleksandra (Management and Administration Journal, 2019)
The paper describes the tools of marketing communication with e-customers and trendsconcerning e-commerce. Special attention has been paid to personalization and recommender systems.The paper treats the characteristics of consumer behaviours on the business-to-customermarket and the main barriers in customer relationship management. In this context the relationshipwith e-customers and the tools of marketing communication in electronic customer relationship havebeen described. The rapid growth of e-commerce has created product overload where customers onthe Web are no longer able to effectively choose the products they are exposed to. There is a lot ofimperfect information and a large supply available for consumers, and so it is extremely difficult toidentify their own needs and preferences and ways for satisfying them. Recommendations are a typeof communication and an especially important issue in e-marketing. It is easy to find many websiteswhere a customer needs advice before taking the decision to purchase a product. Therefore, recommendationsare a powerful tool to assist customers in these decisions. The paper refers to the challengesresulting from the growing importance of network and virtual communities, where the consumeris perceived as a value co-creator.